Determining Turkish migration to Austria: the role of migration policy - Atac, Ilker (Migration Letters, 2014)
Migration from Turkey to Austria started as “guest worker” labour migration. Soon, however, there were signs of permanent immigration from Turkey to Austria leading to a permanent migration in which the differences between labour and family migration began to blur. How can we explain Turkish migration and its shifting dynamics to Austria from a historical perspective? Which factors have played a role in shaping this migration? Turkish migration to Austria offers an interesting case for a discussion of migration policy outcomes since Austria has been a good example of a country with restrictive policies in European comparison. Austrian government policies were of major importance for determining the migratory process from Turkey. However, these were continuously challenged by interventions of the Austrian Constitutional Court, European Court of Human Rights and European Court of Justice. Besides, factors at the individual and meso level, such as family and community networks, and issues connected to economic and political developments in Turkey, shaped migration policy outcomes. After discussing in more detail the various factors that have been identified as influencing migration processes in previous studies, I will examine the interaction of these factors in shaping Turkish migration to Austria, and the role of limiting government policies.